PSYCHOLOGICAL ASPECTS OF MANAGEMENT TOLERANCE OF HEADS OF EDUCATIONAL INSTITUTIONS (Psychology Travelogs, 2024)
The article examines the approach of heads of educational institutions to the relationship with the subjects of pedagogical reality, attention is drawn to individual-typical features of tolerant, tolerant and intolerant attitudes. An important role in working with pupils and teachers is played by understanding and the ability to show tolerance. This concept is defined as the ability to accept others, understand and respect their opinions, differences and peculiarities. Heads of educational institutions should contribute to the creation of an atmosphere of mutual understanding and support. Tolerance, in turn, is defined as the ability to accept the occurrence of thoughts or behavior that do not correspond to one's own beliefs. This is an important aspect in the management of educational processes, as it allows creating space for a diversity of views and approaches. Intolerance, on the contrary, is manifested in the rejection of others and their opinions that do not correspond to one's own ideas. This can lead to conflicts and disharmony in the team, which negatively affects the atmosphere in the institution and the quality of the educational process.The article presents and describes typologies of managers of educational institutions. In particular, the characteristics of the following types are defined and described: «dictator», «snow queen», «fighter», «arrogant», «stoic», «Cinderella», «indulgent», «peaceful», «altruistic». Also, a multi-level program «Psychology and pedagogy of tolerance in the system of improving the qualifications of educational management personnel» has been developed for managers and administrators of educational institutions.Understanding and analyzing the concepts of tolerant interaction help the heads of educational institutions to create a favorable environment for the personal development of both education seekers and the teaching staff in general. Maintaining a tolerant and open approach helps to build relationships based on respect and mutual understanding, which is an important element of successful management of an educational institution.
Keywords: assertiveness; interaction; heads of educational institutions; teacher-manager; patience; tolerance